Cultural Anthropology in English Philosophy - Shigabutdinova Dina Yasavievna; Hasanova Halida Fattoevna (Researchparks Publishing, 2021)
This article discusses in English, cultural anthropology, philosophy in general, the people who contributed to it, their most important work